Integrating Technology Adoption and Workforce Training to Improve Indoor Environmental Quality in Hospital (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Hospitals require optimal Indoor Environmental Quality (IEQ) to promote patient recovery, staff efficiency, and overall well-being. However, the integration of evolving construction technologies into hospital design, construction, operation, and maintenance in many developing regions remains hindered by workforce skill gaps. This paper assessed the level of awareness and adoption of IEQ technology by architects and the awareness level of the users of the space. A mixed-method approach was applied to examine the parameter readings, users’ perceptions, and awareness. Findings reveal that 20% of the selected hospitals made use of passive technology (buoyancy) to enhance air quality, systemic lighting failure, high noise levels, and varying humidity/thermal issues. Only 10% of architect respondents reported using enhancement technologies to improve IEQ metrics beyond air quality. One out of every four user respondents admitted to being unfamiliar with the concept, while only 15% reported being very familiar, and 52.6% of respondents reported being unaware of IEQ monitoring systems. Users are primarily concerned with ventilation, airborne pollutants, and infection control. Recommendations are proposed for embedding IEQ-focused competencies into training curricula and aligning construction policies with global sustainability and healthcare facility standards.